The Effect of Flip PDF Corporate E-Module on Mathematical Concept Understanding of Sixth Grade Elementary School Students - Fery Muhamad Firdaus; Anita Dwi Yani Astuti; Aryna Hana Rahmanda (Universitas Pendidikan Ganesha, 2023)
There is an issue concerning the low understanding of students regarding the concepts of surface area and volume of a sphere. Innovative learning media system is needed to increase students' understanding of mathematical concepts. This study aims to analyze the effect of the use of the Flip PDF Corporate e-module on students’ understanding of the concept of surface area and volume of a sphere. This quantitative research study used a quasi-experimental method with the Pretest - Posttest Control Group Design. The data collection techniques in this research include tests, questionnaires, and observations. The population of this study consists of sixth-grade students from State Elementary School. The research sample includes 15 students from the experimental group and 13 students from the control group, all of whom are from the sixth grade of State Elementary School. The experimental group received treatment in the form of the Flip PDF Corporate e-module and the control group was only given textbooks. The test instrument consisted of 10 multiple-choice questions. Data were analyzed using T-test with the help of the SPSS software. The results of the T-test are in the Sig column. (2-tailed) showed a significant p-value of 0.024. This indicates that H0 is rejected and there is a significant difference in the post-test results between the experimental and the control groups. In other words, the use of Flip PDF Corporate e-module affects the student’s ability to understand the concepts of surface area and volume of a sphere in the sixth grade of State Elementary School.